2012
DOI: 10.1523/jneurosci.6119-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

How Reading in a Second Language Protects Your Heart

Abstract: Reading words in a second language spontaneously activates native language translations in the human bilingual mind. Here, we show that the emotional valence of a word presented in English constrains unconscious access to its Chinese translation. We asked native speakers of Chinese fluent with English to indicate whether or not pairs of English words were related in meaning while monitoring their brain electrical activity. Unbeknownst to the participants, some of the word pairs hid a sound repetition if transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
106
1
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 45 publications
22
106
1
4
Order By: Relevance
“…On this account, Thierry and Wu's (2007) findings reflect this lexical organization rather than parallel activation (i.e., on-line cross-talk). The same argument applies to other studies that use similar logic to Thierry and Wu (Morford et al, 2011;Wu & Thierry, 2012a, 2012Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…On this account, Thierry and Wu's (2007) findings reflect this lexical organization rather than parallel activation (i.e., on-line cross-talk). The same argument applies to other studies that use similar logic to Thierry and Wu (Morford et al, 2011;Wu & Thierry, 2012a, 2012Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
“…Another factor that seems to affect translation equivalents is emotional valence. Wu and Thierry () observed a reduced N400 amplitude when the English prime word had positive or neutral affective valence, but no effect when it had negative valence (e.g., failure ). These two modulating factors of cross‐language activation are worth exploring further, but at present do not posit a challenge for our learning‐based account.…”
Section: Introductionmentioning
confidence: 99%
“…The ERP data demonstrated that Chinese translations of English words were not activated in response to negative English words only. According to the researchers, this finding might indicate that there is a cognitive mechanism that blocks access to the native language meaning of potentially harmful linguistic stimuli (Wu & Thierry, 2012). This finding might partially explain why participants in the present study did not take more time to process negative information in their non-native language, as it would have been predicted by the automatic vigilance hypothesis.…”
Section: Discussionmentioning
confidence: 50%
“…Despite the participants' high proficiency in English and the fact that the absence of an L1 control condition made it impossible to exactly evaluate how native-like the participants actually were, English constituted their second language acquired in a classroom context, which could have had a bearing on the participants' performance. For instance, in a recent study, Wu and Thierry (2012) investigated the role of emotional valence in spontaneous translation in Chinese-English bilinguals. The participants were asked to determine whether two words presented on the screen were related in meaning or not, but they were blind to the fact that some of the English word pairs contained a sound repetition in Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…Emotions conveyed by words in a second language bias the mechanisms of coactivation during written language processing: words with negative valence, but not words with positive or neutral valence, inhibit access to the native language (Wu & Thierry, 2012). In addition to emotions, culturally biased icons/images, recognized as non-linguistic cues, also alter co-activation during speech production (Jared, Poh, & Paivio, 2013;Li, Yang, Suzanne Scherf, & Li, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%